Latin America’s information technologies: promises and realities - Estela Mastromatteo (tripleC: Communication, Capitalism & Critique)
This contribution emphasizes that in order to achieve a real and sustainable human development in Latin America, and for this region to be part of the information society is extremely important to create conditions for a free access to information, education for everyone and  permanently, and a development in science and technology destined to serve society. Access to information and information technology are major promises in this era, but at the same time, become new forms of exclusion. In Latin America the two realities coexist. Is crucial in the solution, to rethink the ethics of information and values that underlie it, respect for human rights, the commitment of societies and our leaders. Highlights the role of libraries as mediators in the production process, organization and retrieval of information access, in safeguarding the freedom of information and the right to free expression through technology, with ethics and values into a real development in Latin America.